Differentiator circuits with scalable and electronically adjustable time constant and their application in phase shift evaluation - Šotner, Roman; Polák, Ladislav; Petržela, Jiří; Semenov, Dmitrii; Langhammer, Lukáš; Jaikla, Winai (Elsevier, 2025)
Two novel scalable and electronically adjustable differentiator designs are presented in this paper. These designs are based on special variable gain amplifiers extending well-known concept of standard single operational amplifier-based differentiators. The key novelty lies in their scalability, which allows for an enhanced time constant value by adjusting the ratio of resistors. Simultaneously, the special form of gain control using a DC voltage offers wide electronic tunability. The solution performs high input and low output impedance, both independent of frequency. Experimental testing demonstrated time constant adjustments in two configurations: from 64 ns to 4.5 mu s (a ratio of maximal and minimal value 70) and from 8.7 mu s to 183 mu s (a ratio of 21). As an application example, the proposed differentiator is utilized in the design of a readout system for an absolute phase shift difference to pulse width ratio converter, suitable for monitoring a very slow phenomenon such biosignals.

Two novel scalable and electronically adjustable differentiator designs are presented in this paper. These designs are based on special variable gain amplifiers extending well-known concept of standard single operational amplifier-based differentiators. The key novelty lies in their scalability, which allows for an enhanced time constant value by adjusting the ratio of resistors. Simultaneously, the special form of gain control using a DC voltage offers wide electronic tunability. The solution performs high input and low output impedance, both independent of frequency. Experimental testing demonstrated time constant adjustments in two configurations: from 64 ns to 4.5 mu s (a ratio of maximal and minimal value 70) and from 8.7 mu s to 183 mu s (a ratio of 21). As an application example, the proposed differentiator is utilized in the design of a readout system for an absolute phase shift difference to pulse width ratio converter, suitable for monitoring a very slow phenomenon such biosignals.
Differentiator circuits with scalable and electronically adjustable time constant and their application in phase shift evaluation
Keywords: Differentiator; Electronic adjustment; Operational amplifier; Scaling; Phase shift measurement; Time constant; Variable gain amplifier; Differentiator; Electronic adjustment; Operational amplifier; Scaling; Phase shift measurement; Time constant; Variable gain amplifier